Intranasal vaccination induced cross-protective secretory IgA antibodies against SARS-CoV-2 variants with reducing the potential risk of lung eosinophilic immunopathology. Issue 41 (29th September 2022) - Hemmi, Takuya; Ainai, Akira; Hashiguchi, Takao; Tobiume, Minoru; Kanno, Takayuki; Iwata-Yoshikawa, Naoko; Iida, Shun; Sato, Yuko; Miyamoto, Sho; Ueno, Akira; Sano, Kaori; Saito, Shinji; et al.
Abstract: To control the coronavirus disease 2019 (COVID-19) pandemic, there is a need to develop vaccines to prevent infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants. One candidate is a nasal vaccine capable of inducing secretory IgA antibodies in the mucosa of the upper respiratory tract, the initial site of infection. However, regarding the development of COVID-19 vaccines, there is concern about the potential risk of inducing lung eosinophilic immunopathology as a vaccine-associated enhanced respiratory disease as a result of the T helper 2 (Th2)-dominant adaptive immune response. In this study, we investigated the protective effect against virus infection induced by intranasal vaccination of recombinant trimeric spike protein derived from SARS-CoV-2 adjuvanted with CpG oligonucleotides, ODN2006, in mouse model. The intranasal vaccine combined with ODN2006 successfully induced not only systemic spike-specific IgG antibodies, but also secretory IgA antibodies in the nasal mucosa. Secretory IgA antibodies showed high protective ability against SARS-CoV-2 variants (Alpha, Beta and Gamma variants) compared to IgG antibodies in the serum. The nasal vaccine of this formulation induced a high number of IFN-γ-secreting cells in the draining cervical lymph nodes and a lower spike-specific IgG1/IgG2a ratio compared to that of subcutaneous vaccination with alum as a typical Th2 adjuvant. These features are consistent with the induction of the Th1 adaptive immune response. In addition, mice intranasally vaccinated with ODN2006 showed less lung eosinophilic immunopathology after viral challenge than mice subcutaneously vaccinated with alum adjuvant. Our findings indicate that intranasal vaccine adjuvanted with ODN2006 could be a candidate that can prevent the infection of antigenically different variant viruses, reducing the risk of vaccine-associated enhanced respiratory disease.